PENGEMBANGAN MATERI PENINGKATAN DAYA INGAT SISWA DALAM BELAJAR - Kasmariadi Dahlan; Rosmawati '; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Unoptimal student achievement caused by poor ability of students toremember the lesson. In that regard the school have an important role in improvingmemory in learning, especially for students in school. But so far the school has notshown efforts to deal with such matters. Therefore, the researchers felt the need todevelop a material on Memory Improvement in Learning is expected to be used by theteacher guidance and counseling to be delivered to students. This material is preparedusing methods of research and development (R & D). The purpose of this research is 1)Establishment of the material in Learning Memory Improvement in terms of clarity,systematics, image support, freshness and completeness of the materials and supportgames / video 2) To determine the quality of material produced. This material isvalidated by the supervisor 1 & 2 teachers and 35 students Counseling SMAN 4Pekanbaru. This material is tested to the student with the allocation of a 3-hour lessons(3 x 45 '). This material consists of the brain and memory, storage system information inmemory, the way the brain stores information, sense memory, the stages of themechanism of memory, the factors that affect memory, activity triggers the effectivenessof memory, and a method to sharpen memory. The results of the development of thismaterial indicates the quality of the material produced is in the category of